Use of Therapeutic LED after Vaporization of Wart Lesions with CO2 Laser: Case Report - Gomes, Isabela Oliveira (2024)
Introduction: The human papillomavirus (HPV) is a sexually transmitted virus, which can lead to the development of lesions on the skin and mucous membranes. A persistent infection can lead to the occurrence of precursor lesions or cancer in different regions, including vulvar lesions. Case report: Descriptive case report of a physiotherapeutic intervention with therapeutic light emitting diode (LED) in a patient with HPV-induced vulvar lesions who underwent an extensive vaporization procedure. After vaporization, she underwent physiotherapeutic treatment with therapeutic LED to accelerate the healing process, tissue regeneration and minimize pain. A LED blanket was used with 18 red LED diodes – 660 nm and 13 infrared LED diodes 850 nm, being the energy delivered by LED of 1 J every 3 minutes, with 10-minute duration. Two applications were performed during hospitalization, one on the first and the other on the second day after surgery. After hospital discharge, two applications, one per week. After the first two applications of LED in the hospital environment, it was possible to observe, in a subjective way, an improvement in local vascularization. There was also an improvement of local pain, urination after applications and reduction of edema reported by the patient. After two once-a-week outpatient applications, satisfactory healing occurred. Conclusion: LED appears to be a promising resource in the healing of lesions in the vulva caused after laser vaporization, however, further controlled clinical studies are needed to confirm this hypothesis.